Pengaruh Articulation Station Hive Terhadap Kemampuan Pengucapan Huruf Apiko Alveolar Pada Anak Tunarungu Kelas IX Tahun Ajaran 2025/2026 Di SLB N 1 Bantul - Sahara, Najwa; Sukadari, Sukadari (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
This research aims to determine the effect of using the Articulation Station Hive learning media on the pronunciation ability of apico alveolar sounds in deaf students in class IX at SLB N 1 Bantul. Deaf children often face communication barriers, which have an impact on their social and educational development. Specific difficulties are experienced when pronouncing apico alveolar sounds such as /t/, /d/, /n/, /l/, and /s/. The existing learning method using a large articulation mirror often disrupts students' concentration, so an alternative medium is needed. This study used a quantitative approach with a One Group Pretest- Posttest design. The research subjects consisted of 4 deaf students in class IX SMPLB. Data was collected through a pronunciation ability test of sounds before (pre-test) and after (post-test) the treatment. The results showed a significant increase in scores after the treatment using the Articulation Station Hive media. The pre-test scores of the four subjects were in the range of 21 to 55, while the post-test scores increased to 48 to 78. The Samples Paired t test showed a significance value of 0.001 (p ≤ 0.05), which indicates that the use of this media has a real effect in improving the pronunciation ability of apico alveolar sounds in deaf children.